Coxsackievirus and Type 1 Diabetes Mellitus: The Wolf's Footprints. (March 2018) - Eizirik, Decio L.; Op de Beeck, Anne
Abstract : Enteroviruses are important environmental contributors to islet inflammation (insulitis) in type 1 diabetes mellitus (T1DM). A recent study characterized the proteomic alterations induced by Coxsackievirus type B (CVB) infection of human islets. This provides relevant information to decipher the words of the virus-induced 'dialog' between β cells and the immune system that leads to autoimmunity.